2021
DOI: 10.1038/s41525-021-00202-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics characteristics of neurogenesis-related gene are dysregulated in tumor immune microenvironment

Abstract: The success of immunotherapy was overshadowed by its low response rate, and the hot or cold tumor microenvironment was reported to be responsible for it. However, due to the lack of an appropriate method, it is still a huge challenge for researchers to understand the molecular differences between hot and cold tumor microenvironments. Further research is needed to gain deeper insight into the molecular characteristics of the hot/cold tumor microenvironment. A large-scale clinical cohort and single-cell RNA-seq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…However, the immune hot type of IS1 had a better survival prognosis than IS5. Moreover, the hot or cold of a tumor was not the only factor that determined the effectiveness of immunotherapy, unlike previous research that only divided tumor cells into the immune cold and hot types [ 23 ]. Our analysis further stratified HCC into 5 immune subgroups, and IS4 with the best prognosis was characterized by immune activity and antitumor genesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the immune hot type of IS1 had a better survival prognosis than IS5. Moreover, the hot or cold of a tumor was not the only factor that determined the effectiveness of immunotherapy, unlike previous research that only divided tumor cells into the immune cold and hot types [ 23 ]. Our analysis further stratified HCC into 5 immune subgroups, and IS4 with the best prognosis was characterized by immune activity and antitumor genesis.…”
Section: Discussionmentioning
confidence: 99%
“…ScRNA-seq analysis is a powerful tool for characterizing the distribution and functional enrichment of various cell subtypes in the tumor microenvironment [ 53 , 54 ]. Michael et al [ 55 ] revealed hundreds of molecularly diverse cell types in the nervous system using single-cell sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al identified several molecular differences between inflamed and noninflamed TMEs using scRNA-seq. These results have profound clinical implications as they may be helpful to the optimization of current combination immunotherapy (54). We also performed scRNA-seq to describe the landscape of PDIA5 in cell subpopulations within diverse cancer types.…”
Section: Discussionmentioning
confidence: 99%